2016
DOI: 10.1097/pcc.0000000000000706
|View full text |Cite
|
Sign up to set email alerts
|

Functional Outcomes and Physical Impairments in Pediatric Critical Care Survivors: A Scoping Review*

Abstract: Functional impairment may be persistent in pediatric survivors of critical care. Unfortunately, studies varied largely in measurement timing and tools used. The lack of differentiation between impairment in different functional domains limited the generalizability of data. Further studies using a combination of standardized measures at various time points of the disease process can help establish more comprehensive rates of physical impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
109
1
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(133 citation statements)
references
References 104 publications
5
109
1
10
Order By: Relevance
“…For example, 89.7% of pediatric critical care survivors admitted in 1995 had a favorable outcome with a likelihood of living independently and 83.6% had a favorable QOL at approximately 3.5 years after discharge as measured by the Health Utilities Index 1 (8) (17). Use of a more liberal definition of morbidity or a global measure with less precision may substantially alter our measured effect (8,27,30). Our study reflects similar results for a broader PICU population.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…For example, 89.7% of pediatric critical care survivors admitted in 1995 had a favorable outcome with a likelihood of living independently and 83.6% had a favorable QOL at approximately 3.5 years after discharge as measured by the Health Utilities Index 1 (8) (17). Use of a more liberal definition of morbidity or a global measure with less precision may substantially alter our measured effect (8,27,30). Our study reflects similar results for a broader PICU population.…”
Section: Discussionsupporting
confidence: 58%
“…Notably, the FSS is not a patient-reported outcome measure but does not require significant training of personnel, lengthy time for administration, or adaptation to growth and developmental norms (23,30). Our assessment tool has the advantage of being easy to administer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent review found that new functional impairment at the time of ICU discharge was reported from 10% to 36% of discharges depending on the methodology used. 6 Evidence detailed below indicates that changes to functional status in critically ill children are tightly linked to physiological dysfunction (severity of illness).…”
Section: What Is Morbidity?mentioning
confidence: 99%
“…6 Depending on the method selected, a child’s deficits in specific domain(s) (e.g. motor ability, communication skills, etc.)…”
Section: Measuring Morbiditymentioning
confidence: 99%